Using the Theory of Planned Behavior to Elicit Restaurant Employee Beliefs about Food Safety: Using Surveys Versus Focus Groups - York, Valerie K.; Brannon, Laura A.; Roberts, Kevin R.; Shanklin, Carol W.; Howells, Amber D. (My University, 2010)
Within the framework of the theory of planned behavior (Ajzen, 1991), this study compared the relative usefulness of utilizing a focus group or survey methodology when eliciting restaurant employees’ beliefs about performing three important food safety behaviors (handwashing, using thermometers, and cleaning and sanitizing work surfaces). Restaurant employees completed both a survey and focus group interview assessing their beliefs about food safety. Results obtained through surveys were observed to be comparable to focus groups, suggesting researchers employ the less expensive and less time-consuming survey methodology. The strengths and weaknesses of each method are discussed. Specific salient beliefs (e.g., advantages, barriers, etc.) about the behaviors offer implications for workplace food safety interventions and training.
Keywords: Food safety; Handwashing; Tthermometers; Cross-contamination; Theory of planned behavior; Focus groups; Surveys; Attitudes; Perceived control; Subjective norms